Maritime Terrorism V. Piracy at Sea: Prevention of Maritime Security Threats and the Responsibility of States to Prevent in the Perspective of International Law - Kultsum, Fatia (Padjadjaran Journal of International Law, 2024)
The sea is used as an alternative spatial medium to realize the interests and goals of each country. Nearly 80% of the world's cargo is transported by sea with more than 112,000 ships manned by more than 1.5 million seafarers. However, the sea is also a vulnerable area to violence, including maritime terrorism and piracy at sea which can threaten maritime security and the national economy if there is no special handling. Several conventions govern the international legal regime, including UNCLOS 1982, the SUA Convention, and the ISPS Code. Under international law, coastal states are responsible and obliged to prevent acts of terrorism by taking necessary measures to enhance their maritime security.